Adverse effects of BDE-47 on in vivo developmental parameters, thyroid hormones, and expression of hypothalamus-pituitary-thyroid (HPT) axis genes in larvae of the self-fertilizing fish Kryptolebias marmoratus. (June 2017) - Kang, Hye-Min; Lee, Young Hwan; Kim, Bo-Mi; Kim, Il-Chan; Jeong, Chang-Bum; Lee, Jae-Seong
Abstract: 2, 2′, 4, 4′-tetrabromodiphenylether (BDE-47) is known to have the potential to disrupt the thyroid endocrine system in fishes due to its structural similarity to the thyroid hormones triiodothyronine (T3) and thyroxine (T4). However, the effects of BDE-47 on thyroid function in fishes remain unclear. In this study, abnormal development (e.g. deformity, hemorrhaging) and an imbalance in thyroid hormone (TH) homeostasis was shown in the early developmental stages of the mangrove killifish Kryptolebias marmoratus in response to BDE-47 exposure. To examine the thyroid endocrinal effect of BDE-47 exposure in mangrove killifish K. marmoratus larvae, transcript levels of genes involved in TH homeostasis and hypothalamus-pituitary-thyroid (HPT) axis-related genes were measured. The expression of thyroid hormone metabolism-related genes (e.g. deiodinases, UGT1ab ) and HPT axis-related genes was up-regulated and there were significant changes in TH levels ( P  < 0.05) in response to BDE-47 exposure. This study provides insights into the regulation of TH homeostasis at the transcriptional level and provides a better understanding on the potential impacts of BDE-47 on the thyroid endocrine system of fishes. Highlights: Transcript levels of genes involved in TH homeostasis and HPT axis-related genes were measured. The expression of thyroid hormone metabolism-related genes (e.g. deiodinases, UGT1ab ) and HPT axis-related genes was up-regulated. There were significant changes in TH levels ( P  < 0.05) in response to BDE-47 exposure.